LEARNERSÃ¢â¬â¢ PROBLEMS WITH THE TEXTUALITY OF THEIR WRITTEN DISCOURSE - Suprapti, Sri (Language Circle: Journal of Language and Literature, 2009)
The article attempts to provide a real account of problems faced by learners of English in producing a piece of written discourse. So it deals with data of second language acquisition (SLA) not with theory of SLA. A micro study was conducted aiming at finding out what textuality elements are problematic to the learners.The findings, hopefully, may serve as a reflective measure in preparing and focusing on what to be thaught and emphasized in teaching writing courses. Key words: SLA, textuality, written discourse, grammatical cohesion, lexical cohesion.